2015
DOI: 10.1177/1934578x1501001131
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided Isolation of Antiproliferative Triterpenoids from Euonymus alatus Twigs

Abstract: Euonymus alatus (Celastraceae) has been used as an anticancer agent in Korean traditional medicine. However, the potential bioactive contributors to the anticancer effects have not been thoroughly studied. Our screening test revealed that the MeOH extract of E. alatus twigs exhibited significant cytotoxicity against A549, SK-OV-3, and SK-MEL-2 cell lines. A bioassay-guided separation of the MeOH extract of E. alatus twigs resulted in the isolation and identification of 14 triterpenes as main phytochemicals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The cytotoxicity was evaluated on the basis of the growth inhibitory effects of the isolated compounds Table 2). Betulinic acid (10) is a well-known anticancer agent inhibiting eukaryotic topoisomerase I [36] and its derivatives have been reported to display cytotoxic activity [13,[37][38][39][40]. The acquired cytotoxicity data of compounds 9-11 are consistent with the previous studies.…”
Section: Resultssupporting
confidence: 79%
“…The cytotoxicity was evaluated on the basis of the growth inhibitory effects of the isolated compounds Table 2). Betulinic acid (10) is a well-known anticancer agent inhibiting eukaryotic topoisomerase I [36] and its derivatives have been reported to display cytotoxic activity [13,[37][38][39][40]. The acquired cytotoxicity data of compounds 9-11 are consistent with the previous studies.…”
Section: Resultssupporting
confidence: 79%
“…Other triterpenes include oleanic acid (45), wilforlide A (46) [ 24 ], hop-(22)-29-en-3 β -ol (47) [ 25 ], 3 β -hydroxy-21 α H-hop-22(29)-en-30-ol (48), 2 α ,3 β -dihydroxyurs-12,19-dien-23,28-oic acid (49) [ 21 ], arborinone (50), taraxerol (51) and germanicol (52) [ 22 ], 11-keto- β -boswellic acid (53), acetyl 11-keto- β -boswellic acid (54), camaldulenic acid (55) [ 23 ], 3 β ,28,30-lup-20(29)-ene triol (56), 28,30-dihydroxy-3-oxolup-20(29)-ene (57), glut-5-en-3 β -ol (58), maslinic acid (59), hederagenin (60), 3-oxo-11alpha-methoxyolean-12-ene (61), 3 β -hydroxy-1-oxo-olean-12-en-28-oic acid (62), ursolic acid (63), and 2 α -hydroxy-ursolic acid (64) [ 26 ]. The structures of compounds 45–64 are shown in Figure 1 .…”
Section: Phytochemistrymentioning
confidence: 99%
“…eu-azarolus MAIRE, Ixora coccinea L. (Rubiaceae), Ligustrum lucidum and Eriobotrya japonica. [1][2][3][4][5] Previous study showed that UA is responsible for many biological activities, such as antioxidant, anti-inflammatory, antibacterial, antitumor and hepatoprotection. [6] Recently, UA is of great concern because of its outstanding antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…[10 -12] Apoptosis plays an important role in antitumor activity of UA. It has been well-known that several signal transduction pathway may be involved in UA-induced cell apoptosis, such as 1 These authors made equal contribution to this work.…”
Section: Introductionmentioning
confidence: 99%